Metallicities for more than 10 million stars derived from Gaia BP/RP spectra - Xylakis-Dornbusch, Theodora; Christlieb, Norbert; Hansen, T. T.; Nordlander, T.; Webber, K. B.; Marshall, J. (Astronomy and astrophysics, 2024)
Context: The third Gaia Data Release, which includes BP/RP spectra for 219 million sources, has opened a new window into the exploration of the chemical history and evolution of the Milky Way. The wealth of information encapsulated in these data is far greater than their low resolving power (R ~ 50) would suggest at first glance, as shown in many studies. We zeroed in on the use of these data for the purpose of the detection of “new” metal-poor stars, which are hard to find yet essential for understanding several aspects of the origin of the Galaxy, star formation, and the creation of the elements, among other topics. Aims: We strive to refine a metal-poor candidate selection method that was developed with simulated Gaia BP/RP spectra with the ultimate objective of providing the community with both a recipe to select stars for medium and high resolution observations, and a catalog of stellar metallicities. Methods: We used a dataset comprised of GALAH DR3 and SAGA database stars in order to verify and adjust our selection method to real-world data. For that purpose, we used dereddening as a means to tackle the issue of extinction, and then we applied our fine-tuned method to select metal-poor candidates, which we thereafter observed and analyzed. Results: We were able to infer metallicities for GALAH DR3 and SAGA stars with color excesses up to E(B − V) < 1.5 and an uncertainty of σ[Fe/H]inf ∼ 0.36, which is good enough for the purpose of identifying new metal-poor stars. Further, we selected 26 metal-poor candidates via our method for observations. As spectral analysis showed, 100% of them had [Fe/H] < −2.0, 57% had [Fe/H] < −2.5, and 8% had [Fe/H] < −3.0. We inferred metallicities for these stars with an uncertainty of σ[Fe/H]inf ∼ 0.31, as was proven when comparing [Fe/H]inf to the spectroscopic [Fe/H]. Finally, we assembled a catalog of metallicities for 10 861 062 stars.
Gesehen am 23.06.2025
Online veröffentlicht: 9. Juli 2024